Genomic information in the decision-making process for the training of a high-performance brazilian swimmer: a case report - Bottura, Ricardo Muller; Dentillo, Daniel Blasioli (Frontiers in Genetics, 2025)
Although numerous genetic variations have been associated with athletic profiles and performance, there is limited research on the real-world application of genetic insights in elite athlete training. The aim of this study is to present our 1-year training experience with a high-performing open water marathon swimmer, integrating genomic-based decision-making into training interventions. This case study involves a 23-year-old elite open water marathon swimmer whose primary goal was to qualify for the Absolute World Championships in 2024. The athlete had a consistent competitive history but sought optimized training strategies to enhance performance and secure a top position in national and international competitions. To personalize the training plan, twenty genetic polymorphisms were analyzed, guiding adjustments in strength training periodization and endurance capacity development. The interventions included tailored regimens aligned with the athlete’s genetic predispositions, aiming to maximize physiological responses, recovery, and performance. Additionally, longitudinal monitoring of training load was conducted to assess adaptation and optimize workload distribution. The outcome was an improvement in athletic performance, highlighted by a top finish among compatriots and qualification for the Absolute World Championships. This case report demonstrates that genetic-based training, when integrated with structured load monitoring, can be an effective strategy to assist sports professionals in planning and optimizing training for high-performance athletes. This approach enhances precision in training interventions, providing valuable support for decision-making in elite sports preparation.